Leaching Characteristics and Potential Ecological Risks of Typical Heavy Metals in Gangue-Based Composite Materials - Yang Yansheng; Qin Yu; He Ruimin; Zhang Jie; Yu Yan (E3S Web of Conferences)
Coal gangue can potentially release varying amounts of heavy metals under conditions such as soaking and leaching, posing a threat to ecological and environmental safety. This has become a research hotspot in recent years. Therefore, this study mainly focused on coal gangue and its composites, and studied the leaching behavior of typical heavy metals under different initial p H conditions and the potential ecological risk of leaching solution and its effect on alfalfa seed germination. The results show that the coal gangue has irregular block and flake structure, and the surface is rough, and its chemical composition mainly includes SiO2 and Al2O3. The leachates from both coal gangue and composite materials were alkaline, with relatively similar pH values. This is attributed to the leaching of alkaline compounds such as CaO and Fe2O3. As the initial pH decreased, the leaching amounts of Pb, Cr, Cd, and Hg increased, while the leaching amount of As decreased. In the leachate from coal gangue, the single-factor pollution index and Nemerow pollution index for Pb were 0.53 and 0.54, respectively. The composite materials demonstrated a good stabilization effect on heavy metals. These findings can provide a reference for the safe disposal of coal gangue in mining areas.